Genetic resistance to helminths in small ruminants in Africa - (:unkn) unknown (My University, 1997)
Some local breeds of cattle, sheep and goats are genetically resistant and/or tolerant to internal parasites. In this article the data concerning within and between breed genetic variability in resistance to helminths in tropical ruminants are reviewed. The main research projects in Kenya, Ethiopia and Senegal of the International Livestock Research Institute on genetic resistance to strongyles in small ruminants are also presented. Red Maasai sheep are more resistant to internal parasites than Dorper sheep on the humid eastern coast of Kenya. Within breed variations have been shown. It seems that economic gains may result from the introduction of resistant sheep breeds in this part of Kenya. Small East African goats have been found to be more resistant than Galla goats. In Ethiopia (Debre berhan, 1780 m), no difference was found in resistance to internal parasites between Menz sheep (local breed) and Horro sheep (breed from the small hills region). However, within breeds variability exists and seems promising for selection. In Senegal, a project in collaboration with CIRAD-EMVT and ISRA, investigations on internal parasites of small ruminants were carried out in farms since 1992 in the northern arid region (Louga, Fulani sheep and Sahel goats) and in the southern humid region (Kolda, Djallonke sheep and West African Dwarf goats). In the experimental station of Kolda, a mating plan with animals identified during farm surveys as low and high responders, has been set up to estimate genetic parameters of resistance to digestive strongyles in Djallonke sheep.
Keywords: African Research